Comparative mapping of on-targets and off-targets for the discovery of anti-trypanosomatid folate pathway inhibitors - Panecka-Hofman, Joanna; Wade, Rebecca C. (Biochimica et biophysica acta. General subjects, 2017)
Background Multi-target approaches are necessary to properly analyze or modify the function of a biochemical pathway or a protein family. An example of such a problem is the repurposing of the known human anti-cancer drugs, antifolates, as selective anti-parasitic agents. This requires considering a set of experimentally validated protein targets in the folate pathway of major pathogenic trypanosomatid parasites and humans: (i) the primary parasite on-targets: pteridine reductase 1 (PTR1) (absent in humans) and bifunctional dihydrofolate reductase-thymidylate synthase (DHFR-TS), (ii) the primary off-targets: human DHFR and TS, and (iii) the secondary on-target: human folate receptor β, a folate/antifolate transporter. Methods we computationally compared the structural, dynamic and physico-chemical properties of the targets. We based our analysis on available inhibitory activity and crystallographic data, including a crystal structure of the bifunctional T. cruzi DHFR-TS with tetrahydrofolate bound determined in this work. Due to the low sequence and structural similarity of the targets analyzed, we employed a mapping of binding pockets based on the known common ligands, folate and methotrexate. Results Our analysis provides a set of practical strategies for the design of selective trypanosomatid folate pathway inhibitors, which are supported by enzyme inhibition measurements and crystallographic structures. Conclusions the ligand-based comparative computational mapping of protein binding pockets provides a basis for repurposing of anti-folates and the design of new anti-trypanosmatid agents. General significance apart from the target-based discovery of selective compounds, our approach may be also applied for protein engineering or analyzing evolutionary relationships in protein families.
Gesehen am 05.06.2018